An all-solid-state battery

By introducing silicone oil into the solid electrolyte layer of all-solid lithium batteries and distribute its content in a gradient decrease in the direction away from the negative electrode sheet, the problems of uneven deposition of lithium metal and lithium dendrites are solved, and the battery is more stable and Efficient lithium ion transfer improves the overall performance of the battery.

CN116826155BActive Publication Date: 2025-02-14CALB GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310879594.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-07-17
Publication Date
2025-02-14
Estimated Expiration
2043-07-17

AI Technical Summary

Technical Problem

In all-solid lithium batteries, due to the lack of fluidity of solid electrolytes, lithium metal is unevenly deposited, forming lithium dendrites, which in turn affects the stability and electrochemical performance of the battery.

Method used

Silicone oil is introduced into the solid electrolyte layer, and its content is distributed in a gradient decrease in the direction away from the negative electrode sheet to improve the contact effect between the negative electrode sheet and the solid electrolyte, reduce the interface impedance, and promote uniform deposition of lithium ions.

Benefits of technology

By introducing silicone oil and controlling its gradient distribution, the formation of lithium dendrites can be effectively prevented, the structural stability of the battery and the dynamic transmission characteristics of lithium ion are improved, thereby improving the conductivity and cycling performance of all-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116826155B_ABST
    Figure CN116826155B_ABST
Patent Text Reader

Abstract

This invention provides an all-solid-state battery, comprising a positive electrode, a negative electrode, and a solid electrolyte layer. The solid electrolyte layer is disposed between the positive and negative electrodes and includes an electrolyte material and silicone oil. Along the thickness direction of the solid electrolyte layer, the silicone oil content exhibits a gradient distribution from the negative electrode side to the positive electrode side, with a higher silicone oil content near the negative electrode side than near the positive electrode side. By introducing silicone oil into the solid electrolyte layer and setting the silicone oil content to decrease gradually away from the negative electrode, this invention ensures that lithium ions rapidly migrate from the positive electrode during charging and then uniformly deposit on the negative electrode surface, preventing the formation of lithium dendrites and improving the electrochemical and safety performance of the all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to an all-solid-state battery. Background Art

[0002] In recent years, all-solid-state lithium batteries have received extensive attention due to their high stability and safety. Compared with lithium-ion batteries using flammable electrolytes, all-solid-state batteries use thinner and lighter solid electrolytes and solid lithium metal electrodes, which greatly reduce the overall size and weight of the battery and are safer. In addition, the combination of solid electrolytes and lithium metal anodes is expected to achieve higher energy density. However, in all-solid-state batteries, due to the lack of fluidity of solid electrolytes, the poor solid-solid interface contact, defects, and pores between solid electrolytes and lithium metal anodes easily lead to uneven deposition of metallic lithium, which evolves into lithium dendrites. Lithium dendrites are thin, branch-like metal filaments, which are tiny tree-like defects formed on the lithium anode after multiple charge and discharge cycles of the battery. The growth of lithium dendrites will cause the battery to be unstable during the cycle and cause irreversible deposition of metallic lithium, thereby reducing the electrochemical performance of the battery. If lithium dendrites continue to grow and contact the positive electrode, it will cause a short circuit in the battery, which limits the application of all-solid-state lithium batteries.

[0003] Therefore, how to improve the interface contact between the solid electrolyte and the negative electrode, induce uniform deposition of lithium, and prevent the formation of lithium dendrites due to its uneven deposition has become an important problem that the vast majority of lithium-ion battery scientific researchers urgently need to solve. Summary of the invention

[0004] In order to solve the problems and shortcomings existing in the prior art, the present invention provides an all-solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, the solid electrolyte layer is arranged between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte layer comprises an electrolyte material and silicone oil; in the thickness direction of the solid electrolyte layer, the silicone oil content is distributed in a gradient from the negative electrode sheet side to the positive electrode sheet side, and the silicone oil content on the side close to the negative electrode sheet is greater than the silicone oil content on the side close to the positive electrode sheet.

[0005] The all-solid-state battery provided by the present invention introduces silicone oil into the solid electrolyte layer. The molecular structure of the silicone oil contains Si, O and a small amount of H atoms. On the one hand, it can form chemical bonds with strong affinity with P, S and Cl in the electrolyte material, so that the solid electrolyte layer has good mechanical properties and structural stability; on the other hand, the Si-O bond can ensure the rapid migration of lithium ions in the solid electrolyte layer, thereby making the all-solid-state battery have excellent cycle performance.

[0006] At the same time, the silicone oil is controlled to have a higher content on the side close to the negative electrode sheet than on the side close to the positive electrode sheet, that is, the content of the silicone oil is distributed in a gradient decreasing direction away from the negative electrode sheet. On the one hand, due to the poor solid-solid interface contact between the solid electrolyte and the negative electrode, it is easy to cause uneven lithium deposition. The present invention controls the content of silicone oil to be distributed in a gradient decreasing direction away from the negative electrode sheet, which can improve the contact effect between the negative electrode sheet and the solid electrolyte, reduce the interface impedance, and effectively guide the lithium ions to be uniformly deposited on the surface of the negative electrode sheet, thereby preventing the generation of lithium dendrites on the surface of the negative electrode. The silicone oil is filled in the gaps between the particles in the solid electrolyte layer near the negative electrode, which can further prevent the formation of lithium dendrites. On the other hand, the present invention controls the silicone oil content on the side close to the positive electrode sheet to be lower, so that the porosity of the solid electrolyte layer near the positive electrode is higher, which can promote the rapid migration of lithium ions from the positive electrode during the charging process, and then uniformly deposit on the surface of the negative electrode. Therefore, the all-solid-state battery provided by the present invention has good structural stability and lithium ion kinetic transmission characteristics during the charging and discharging process, so that the all-solid-state battery has excellent conductivity and cycle performance.

[0007] If the silicone oil content on the side close to the positive electrode sheet is higher than or equal to the silicone oil content on the side close to the negative electrode sheet, that is, the silicone oil content is distributed in a gradient increasing or uniform distribution in the direction away from the negative electrode sheet, so that the silicone oil content on the side close to the positive electrode sheet of the solid electrolyte layer is higher and the porosity is lower, which is not conducive to the rapid migration of lithium ions from the positive electrode during charging, and the low content silicone oil close to the negative electrode side is difficult to effectively induce lithium to be uniformly deposited on the negative electrode surface, and even causes it to evolve into lithium dendrites; at the same time, the silicone oil with a higher content close to the positive electrode side has little effect on improving the interface contact between the electrolyte and the positive electrode sheet, but it is easy to cause the silicone oil to undergo side reactions such as oxidation reaction under the catalysis of the positive electrode, resulting in a higher impedance of the battery. Therefore, the all-solid-state battery provided by the present invention introduces silicone oil into the solid electrolyte layer, and sets the silicone oil content in the solid electrolyte layer to be distributed in a gradient decreasing direction away from the negative electrode sheet, ensuring that lithium ions migrate quickly from the positive electrode during charging of the solid-state battery, and then uniformly deposit on the negative electrode surface, preventing the generation of lithium dendrites, and improving the electrochemical performance and safety performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 Element distribution map (SEM-mapping) of the battery prepared in Example 1;

[0009] Figure 2 Element distribution map (SEM-mapping) of the battery prepared for Comparative Example 2. DETAILED DESCRIPTION

[0010] The present invention provides an all-solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, wherein the solid electrolyte layer is arranged between the positive electrode sheet and the negative electrode sheet, and the solid electrolyte layer comprises an electrolyte material and silicone oil; in the thickness direction of the solid electrolyte layer, the silicone oil content is distributed in a gradient from the negative electrode sheet side to the positive electrode sheet side, and the silicone oil content on the side close to the negative electrode sheet is greater than the silicone oil content on the side close to the positive electrode sheet.

[0011] The all-solid-state battery provided by the present invention introduces silicone oil into the solid electrolyte layer. The molecular structure of the silicone oil contains Si, O and a small amount of H atoms. On the one hand, it can form chemical bonds with strong affinity with P, S and Cl in the electrolyte material, so that the solid electrolyte layer has good mechanical properties and structural stability; on the other hand, the Si-O bond can ensure the rapid migration of lithium ions in the solid electrolyte layer, thereby making the all-solid-state battery have excellent cycle performance.

[0012] At the same time, the silicone oil is controlled to have a higher content on the side close to the negative electrode sheet than on the side close to the positive electrode sheet, that is, the content of the silicone oil is distributed in a gradient decreasing direction away from the negative electrode sheet. On the one hand, due to the poor solid-solid interface contact between the solid electrolyte and the negative electrode, it is easy to cause uneven lithium deposition. The present invention controls the content of silicone oil to be distributed in a gradient decreasing direction away from the negative electrode sheet, which can improve the contact effect between the negative electrode sheet and the solid electrolyte, reduce the interface impedance, and effectively guide the lithium ions to be uniformly deposited on the surface of the negative electrode sheet, thereby preventing the generation of lithium dendrites on the surface of the negative electrode. The silicone oil is filled in the gaps between the particles in the solid electrolyte layer near the negative electrode, which can further prevent the formation of lithium dendrites. On the other hand, the present invention controls the silicone oil content on the side close to the positive electrode sheet to be lower, so that the porosity of the solid electrolyte layer near the positive electrode is higher, which can promote the rapid migration of lithium ions from the positive electrode during the charging process, and then uniformly deposit on the surface of the negative electrode. Therefore, the all-solid-state battery provided by the present invention has good structural stability and lithium ion kinetic transmission characteristics during the charging and discharging process, so that the all-solid-state battery has excellent conductivity and cycle performance.

[0013] If the silicone oil content on the side close to the positive electrode sheet is higher than or equal to the silicone oil content on the side close to the negative electrode sheet, that is, the silicone oil content is distributed in a gradient increasing or uniform distribution in the direction away from the negative electrode sheet, so that the silicone oil content on the side close to the positive electrode sheet of the solid electrolyte layer is higher and the porosity is lower, which is not conducive to the rapid migration of lithium ions from the positive electrode during charging, and the low content silicone oil close to the negative electrode side is difficult to effectively induce lithium to be uniformly deposited on the negative electrode surface, and even causes it to evolve into lithium dendrites; at the same time, the silicone oil with a higher content close to the positive electrode side has little effect on improving the interface contact between the electrolyte and the positive electrode sheet, but it is easy to cause the silicone oil to undergo side reactions such as oxidation reaction under the catalysis of the positive electrode, resulting in a higher impedance of the battery. Therefore, the all-solid-state battery provided by the present invention introduces silicone oil into the solid electrolyte layer, and sets the silicone oil content in the solid electrolyte layer to be distributed in a gradient decreasing direction away from the negative electrode sheet, ensuring that lithium ions migrate quickly from the positive electrode during charging of the solid-state battery, and then uniformly deposit on the negative electrode surface, preventing the generation of lithium dendrites, and improving the electrochemical performance and safety performance of the all-solid-state battery.

[0014] Preferably, the content of silicone oil accounts for 1-5% of the total mass of the solid electrolyte layer.

[0015] Preferably, on the surface of the solid electrolyte layer close to the negative electrode sheet, the ratio of the area of ​​the solid electrolyte layer containing silicone oil to the total area of ​​the solid electrolyte layer is S, and S satisfies: 35%≤S<100%. By setting the ratio of the area of ​​the solid electrolyte layer containing silicone oil to the total area of ​​the solid electrolyte layer within a reasonable range, the silicone oil is distributed in a non-full coverage manner in the solid electrolyte layer, which is conducive to the silicone oil filling the depressions and pores of the solid electrolyte layer, reducing the defects and pores inside and on the surface of the solid electrolyte layer, making the solid electrolyte layer uniform and flat, improving the contact effect between the solid electrolyte and the negative electrode sheet, inducing lithium ions to achieve uniform deposition on the surface of the negative electrode sheet, avoiding the generation of lithium dendrites, and thus improving the cycle stability and safety performance of the all-solid-state battery; at the same time, this will not hinder the direct contact between the solid electrolyte layer and the negative electrode sheet, so that the internal resistance of the electrode sheet is at a low level, ensuring the conductive performance of the all-solid-state battery.

[0016] Preferably, S satisfies: 50%≤S≤90%.

[0017] Preferably, the thickness of the solid electrolyte layer is 10 to 60 μm. If the thickness of the solid electrolyte layer is too thin, the solid electrolyte content it contains is too little, processing is difficult, and the safety performance and structural stability of the prepared battery are reduced; if the thickness of the solid electrolyte layer is too thick, the battery has a higher impedance, which deteriorates the cycle performance of the battery. In the present invention, by controlling the thickness of the solid electrolyte layer within the above range, the electrochemical performance of the battery can be further improved while ensuring the processing performance of the solid electrolyte layer.

[0018] Preferably, in the solid electrolyte layer, the ratio of the thickness of the solid electrolyte layer containing silicone oil to the total thickness of the solid electrolyte layer is L, and L satisfies: 40%≤L<100%. The ratio L of the thickness of the solid electrolyte layer containing silicone oil to the total thickness of the solid electrolyte layer is controlled within the above range, so that the improvement effect of silicone oil on the solid-solid interface contact between the solid electrolyte and the negative electrode sheet can be ensured, and at the same time, the direct contact between the solid electrolyte layer and the negative electrode sheet will not be hindered, so that the internal resistance of the electrode sheet is at a lower level, thereby improving the cycle performance and conductivity of the all-solid-state battery obtained thereby.

[0019] Preferably, in the solid electrolyte layer, the side close to the positive electrode sheet does not contain silicone oil.

[0020] Preferably, the electrolyte material includes an inorganic solid electrolyte, and the inorganic solid electrolyte includes at least one of an oxide electrolyte and a sulfide electrolyte.

[0021] Specifically, oxide electrolytes include perovskite-type solid electrolytes, LISICON-type solid electrolytes, NASICON-type solid electrolytes, and garnet-type solid electrolytes;

[0022] Specifically, sulfide electrolytes include LiPSX, Li 7-x-y PS 6-x-y CxBr y (0≤x≤2,0≤y≤2), Li2S-P2S5, Li a M b PS c (a+4b+5=2c, 0≤b≤1), Li6PSX; wherein the X element refers to at least one of F, Cl, Br, I; and the M element refers to at least one of SI, Ge, Sn.

[0023] Preferably, the positive electrode active material contained in the positive electrode sheet includes a lithium-containing metal oxide, and the general chemical formula of the lithium-containing metal oxide is LiNi 1-x-y Co x M y O2, where 0≤x≤0.5, 0≤y≤0.5.

[0024] Preferably, the negative electrode active material contained in the negative electrode sheet is at least one of lithium metal and lithium alloy.

[0025] Example 1

[0026] This embodiment provides an all-solid-state battery, and the preparation method thereof comprises the following steps:

[0027] 1. Preparation of positive electrode:

[0028] NCM90、Li 5.5PS 4.5 Cl 1.5 , gas phase carbon fiber, and hydrogenated styrene butadiene rubber were mixed in a mass ratio of 85:8:4:3. The slurry was prepared using solvent xylene and coated on the surface of carbon-coated aluminum foil with a coating thickness of 100 μm, and then dried in a drying oven at 60°C for 12 hours to obtain a positive electrode sheet.

[0029] 2. Preparation of solid electrolyte layer:

[0030] Weigh 5g of inorganic solid electrolyte Li 5.5 PS 4.5 Cl 1.5 , 0.05g binder SBR, configured into slurry with xylene and coated on the surface of the above-mentioned positive electrode sheet, the coating thickness is 43μm, and then preliminarily dried in a drying oven at 25℃ and a dew point temperature of -45℃ for 1h, and then dried in a drying oven at 60℃ for 12h to obtain a solid electrolyte intermediate; then 0.15g silicone oil is coated on the side of the above-mentioned solid electrolyte intermediate away from the above-mentioned positive electrode sheet, the coating thickness is controlled to be 1μm, dried in a drying oven at 60℃ for 12h, and then rolled at a rolling pressure of 15 tons and a rolling temperature of 25℃ to obtain a solid electrolyte layer with a thickness of 43μm.

[0031] 3. Choice of negative electrode:

[0032] In this embodiment, a lithium sheet is selected as the negative electrode sheet of the all-solid-state battery;

[0033] 4. Assemble the battery:

[0034] The positive electrode sheet coated with the solid electrolyte layer is cut into 45*60mm electrode sheets by a slicer, and then a lithium sheet is stacked on the side of the solid electrolyte layer away from the positive electrode sheet to form a stacked structure in which the positive electrode sheet, the solid electrolyte layer, and the negative electrode sheet are arranged in sequence to assemble the all-solid-state battery of this embodiment.

[0035] The battery prepared in this example was subjected to SEM-mapping test, and the test results are as follows: Figure 1 As shown. Figure 1 It can be seen that in the solid electrolyte layer, the silicone oil content on the side close to the negative electrode sheet is greater than the silicone oil content on the side close to the positive electrode sheet.

[0036] Example 2

[0037] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in structure is that in the process of preparing the solid electrolyte layer, the rolling pressure is 18 tons and the rolling temperature is 30° C. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0038] Example 3

[0039] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in structure is that in the process of preparing the solid electrolyte layer, the rolling pressure is 12 tons and the rolling temperature is 25° C. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0040] Example 4

[0041] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in structure is that in the process of preparing the solid electrolyte layer, the rolling pressure is 10 tons and the rolling temperature is 20° C. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0042] Example 5

[0043] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in structure is that in the process of preparing the solid electrolyte layer, the rolling pressure is 20 tons and the rolling temperature is 35° C. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0044] Example 6

[0045] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in structure is that in the process of preparing the solid electrolyte layer, the rolling pressure is 22 tons and the rolling temperature is 50° C. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0046] Example 7

[0047] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in structure is that in the process of preparing the solid electrolyte layer, the rolling pressure is 5 tons and the rolling temperature is 20° C. In addition to the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0048] Example 8

[0049] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in composition is that in the process of preparing the solid electrolyte layer, the content of silicone oil is 0.05 g. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0050] Example 9

[0051] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in composition is that in the process of preparing the solid electrolyte layer, the content of silicone oil is 0.25 g. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0052] Example 10

[0053] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in composition is that in the process of preparing the solid electrolyte layer, the content of silicone oil is 0.0045 g. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0054] Embodiment 11

[0055] This embodiment prepares an all-solid-state battery with reference to embodiment 1. Compared with embodiment 1, the difference in composition is that in the process of preparing the solid electrolyte layer, the content of silicone oil is 0.255 g. Except for the above differences, the materials, formula ratios and preparation operations used in this embodiment are strictly consistent with those in embodiment 1.

[0056] Comparative Example 1

[0057] This comparative example provides an all-solid-state battery, and its preparation method comprises the following steps:

[0058] 1. Choice of negative electrode:

[0059] In this comparative example, a lithium sheet is selected as the negative electrode sheet of the all-solid-state battery.

[0060] 2. Preparation of solid electrolyte layer:

[0061] Weigh 5g of inorganic solid electrolyte Li 5.5 PS 4.5 Cl 1.5 , 0.05g of binder SBR, prepared into a slurry with xylene and coated on the surface of the above-mentioned negative electrode sheet, with a coating thickness of 43μm, and then preliminarily dried in a drying oven at 25℃ and a dew point temperature of -45℃ for 1h, and then dried in a drying oven at 60℃ for 12h to obtain a solid electrolyte intermediate; then 0.15g of silicone oil was coated on the side of the above-mentioned solid electrolyte intermediate away from the above-mentioned negative electrode sheet, and the coating thickness was controlled to be 1μm, and dried in a drying oven at 60℃ for 12h, and then rolled at a rolling pressure of 15 tons and a rolling temperature of 25℃ to obtain a solid electrolyte layer with a thickness of 43μm.

[0062] 3. Preparation of positive electrode:

[0063] NCM90、Li 5.5 PS 4.5Cl 1.5 , gas phase carbon fiber, and hydrogenated styrene butadiene rubber were mixed in a mass ratio of 85:8:4:3. The slurry was prepared using solvent xylene and coated on the surface of carbon-coated aluminum foil with a coating thickness of 100 μm, and then dried in a drying oven at 60°C for 12 hours to obtain a positive electrode sheet.

[0064] 4. Assemble the battery:

[0065] The positive electrode sheet coated with the solid electrolyte layer is cut into 45*60mm electrode sheets by a slicer, and then a lithium sheet is stacked on the side of the solid electrolyte layer away from the positive electrode sheet to form a stacked structure in which the positive electrode sheet, the solid electrolyte layer, and the negative electrode sheet are arranged in sequence to assemble the all-solid-state battery of this embodiment.

[0066] In the solid electrolyte layer of this comparative example, the content of silicone oil on the side close to the negative electrode sheet is less than the content of silicone oil on the side close to the positive electrode sheet.

[0067] Comparative Example 2

[0068] This comparative example prepares an all-solid-state battery with reference to Example 1. Compared with Example 1, the difference in structure is that the rolling pressure is 3 tons. In addition to the above differences, the materials, formula ratios and preparation operations used in this comparative example are strictly consistent with those in Example 1.

[0069] The battery prepared in this comparative example was subjected to SEM-mapping test, and the test results are as follows: Figure 2 As shown. Figure 2 It can be seen that in the solid electrolyte layer of this comparative example, the silicone oil content on the side close to the negative electrode sheet is equal to the silicone oil content on the side close to the positive electrode sheet.

[0070] Comparative Example 3

[0071] This comparative example provides an all-solid-state battery, and its preparation method comprises the following steps:

[0072] 1. Preparation of positive electrode:

[0073] NCM90、Li 5.5 PS 4.5 Cl 1.5 , gas phase carbon fiber, and hydrogenated styrene butadiene rubber were mixed in a mass ratio of 85:8:4:3. The slurry was prepared using solvent xylene and coated on the surface of carbon-coated aluminum foil with a coating thickness of 100 μm, and then dried in a drying oven at 60°C for 12 hours to obtain a positive electrode sheet.

[0074] 2. Preparation of solid electrolyte layer:

[0075] Weigh 5g of inorganic solid electrolyte Li 5.5 PS 4.5 Cl 1.5, 0.05g binder SBR, prepared into slurry with xylene and coated on the surface of the above-mentioned positive electrode sheet with a coating thickness of 43μm, and then preliminarily dried in a drying oven at 25℃ and a dew point temperature of -45℃ for 1h, and then dried in a drying oven at 60℃ for 12h to obtain a solid electrolyte intermediate; then rolled at a rolling pressure of 15 tons and a rolling temperature of 25℃ to obtain a solid electrolyte layer with a thickness of 43μm.

[0076] 3. Choice of negative electrode:

[0077] In this comparative example, a lithium sheet is selected as the negative electrode sheet of the all-solid-state battery;

[0078] 4. Assemble the battery:

[0079] The positive electrode sheet coated with the solid electrolyte layer is cut into 45*60mm electrode sheets by a slicer, and then a lithium sheet is stacked on the side of the solid electrolyte layer away from the positive electrode sheet to form a stacked structure in which the positive electrode sheet, the solid electrolyte layer, and the negative electrode sheet are arranged in sequence, and an all-solid-state battery of the comparative example is assembled.

[0080] Test Case

[0081] 1. Participants

[0082] This test example uses the all-solid-state batteries prepared in Examples 1 to 11 and Comparative Examples 1 to 3 as test objects of this test example.

[0083] 2. Test content

[0084] (1) Gradient distribution of silicone oil, ratio of the area of ​​the solid electrolyte layer containing silicone oil to the total area of ​​the solid electrolyte layer, and ratio of the thickness of the solid electrolyte layer containing silicone oil to the total thickness of the solid electrolyte layer: The participating batteries were subjected to SEM-mapping test;

[0085] (2) Gram capacity and first efficiency: At 25°C, the voltage range is set to 2.75-4.3V. The battery under test is charged and discharged at a rate of 0.33C. The first cycle charge and discharge capacity is recorded and the first efficiency is calculated. The gram capacity is calculated based on the electrode weight.

[0086] (3) Capacity retention rate: At 25°C, the voltage range was set to 2.75-4.3V. The battery under test was charged and discharged at a rate of 1C. A full charge and discharge cycle test was performed for 1000 cycles, and the capacity retention rate was recorded.

[0087] (4) DC impedance: The battery under test was cycled to 200 cls at 25°C, the battery was charged to 50% SOC, and discharged at a current rate of 1C for 18 s. The battery voltage U2, current I before discharge termination, and battery voltage U1 after the battery voltage stabilized were recorded. The DC impedance was calculated according to the formula R = (U2-U1) / I;

[0088] 3. Test results

[0089] Table 1. Structural test results of all-solid-state batteries of Examples 1 to 11 and Comparative Examples 1 to 3

[0090]

[0091]

[0092]

[0093] Table 2. Relevant performance test results of all-solid-state batteries of Examples 1 to 11 and Comparative Examples 1 to 3

[0094]

[0095]

[0096] The test results are shown in Table 1. By comparing the performance test results corresponding to Examples 1 to 11 with those of Comparative Example 3, it can be found that the impedance of the batteries prepared in Examples 1 to 11 is significantly lower than that of Comparative Example 3, and the capacity retention rate after 300 cycles is significantly lower than that of Comparative Example 3. The reason is that the all-solid-state batteries prepared in Examples 1 to 11 introduce silicone oil into the solid electrolyte layer, and the silicone oil can make the solid electrolyte layer have better mechanical properties and structural stability, and at the same time, can ensure the rapid migration of lithium ions in the solid electrolyte layer, thereby improving the cycle performance of the all-solid-state battery prepared thereby.

[0097] Comparing the performance test results corresponding to Examples 1 to 11 with those of Comparative Examples 1 to 2, it can be found that the impedance of the battery prepared in Examples 1 to 11 is significantly lower than that of Comparative Examples 1 to 2, and the capacity retention rate after 300 cycles is significantly higher than that of Comparative Examples 1 to 2. The reason is that in the solid electrolyte layer of the all-solid-state battery prepared in Comparative Examples 1 to 2, the silicone oil content on the side close to the negative electrode sheet is ≤ the silicone oil content on the side close to the positive electrode sheet, so that the silicone oil content on the side close to the positive electrode sheet of the solid electrolyte layer is high and the porosity is low, which is not conducive to the rapid migration of lithium ions from the positive electrode during charging, and the low content of silicone oil on the side close to the negative electrode is difficult to effectively induce lithium to be uniformly deposited on the surface of the negative electrode, and even causes it to evolve into lithium dendrites; at the same time, the silicone oil with a higher content on the side close to the positive electrode of the solid electrolyte layer is prone to oxidation reactions and other side reactions under the catalysis of the positive electrode, resulting in the impedance of the battery at a higher level. Therefore, both of these situations will lead to the silicone oil being unable to effectively play a good role in improving the interface contact and reducing the interface impedance in the negative electrode sheet and the solid electrolyte layer, which is not conducive to the cycle performance of the solid-state battery.

[0098] By comparing the performance test results corresponding to Example 1 with those of Examples 6, 7, and 11, it can be found that the impedance of the battery prepared in Example 1 is lower than that of Examples 6, 7, and 11; the gram capacity, first efficiency, and capacity retention rate after 300 cycles are higher than those of Examples 6, 7, and 11, which shows that the ratio S of the area of ​​the solid electrolyte layer containing silicone oil to the total area of ​​the solid electrolyte layer also has a great influence on the conductivity and cycle performance of the solid-state battery finally prepared. The reason is that the ratio S of the area of ​​the solid electrolyte layer containing silicone oil to the total area of ​​the solid electrolyte layer is controlled within a certain range, so that the silicone oil is distributed in the solid electrolyte layer in a non-full coverage manner, which is conducive to the filling of silicone oil in the depressions and pores of the solid electrolyte layer, making the solid electrolyte layer uniform and flat, improving the contact effect between the solid electrolyte and the negative electrode sheet, inducing lithium ions to achieve uniform deposition on the surface of the negative electrode sheet, and avoiding the generation of lithium dendrites. At the same time, this will not hinder the direct contact between the solid electrolyte layer and the negative electrode sheet, so that the internal resistance of the electrode sheet is at a lower level, thereby improving the cycle performance and conductivity of the all-solid-state battery prepared thereby.

[0099] By comparing the performance test results corresponding to Example 1 with those of Examples 7 and 10, it can be found that when the ratio L of the thickness of the solid electrolyte layer containing silicone oil to the total thickness of the solid electrolyte layer satisfies: 40≤L<100%, the improvement effect on the conductivity and cycle performance of the solid-state battery is good. The reason is that the ratio L of the thickness of the solid electrolyte layer containing silicone oil to the total thickness of the solid electrolyte layer is controlled within a certain range, which can ensure the improvement effect of silicone oil on the solid-solid interface contact between the solid electrolyte and the negative electrode sheet, and at the same time will not hinder the direct contact between the solid electrolyte layer and the negative electrode sheet, so that the internal resistance of the electrode sheet is at a lower level, thereby improving the cycle performance and conductivity of the all-solid-state battery obtained thereby.

[0100] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.

Claims

1. An all-solid-state battery, comprising a positive electrode sheet, a negative electrode sheet and a solid electrolyte layer, wherein the solid electrolyte layer is arranged between the positive electrode sheet and the negative electrode sheet, characterized in that: The solid electrolyte layer comprises electrolyte material and silicone oil; In the thickness direction of the solid electrolyte layer, the silicone oil content is distributed in a gradient from the negative electrode sheet side to the positive electrode sheet side, and the silicone oil content on the side close to the negative electrode sheet is greater than the silicone oil content on the side close to the positive electrode sheet; The ratio of the thickness of the solid electrolyte layer containing silicone oil to the total thickness of the solid electrolyte layer is L, and L satisfies: 40%≤L<100%.

2. The all-solid-state battery according to claim 1, characterized in that: The content of the silicone oil accounts for 1-5% of the total mass of the solid electrolyte layer.

3. The all-solid-state battery according to claim 1, characterized in that: On the surface of the solid electrolyte layer close to the negative electrode sheet, the ratio of the area of ​​the solid electrolyte layer containing silicone oil to the total area of ​​the solid electrolyte layer is S, and S satisfies: 35%≤S<100%.

4. The all-solid-state battery according to claim 3, characterized in that: The S satisfies: 50%≤S≤90%.

5. The all-solid-state battery according to claim 1, characterized in that: The thickness of the solid electrolyte layer is 10 to 60 μm.

6. The all-solid-state battery according to claim 1, characterized in that: In the solid electrolyte layer, the side close to the positive electrode sheet does not contain silicone oil.

7. The all-solid-state battery according to claim 1, characterized in that: The electrolyte material includes an inorganic solid electrolyte, and the inorganic solid electrolyte includes at least one of an oxide electrolyte and a sulfide electrolyte.

8. The all-solid-state battery according to claim 1, characterized in that: The positive electrode active material contained in the positive electrode sheet includes a lithium-containing metal oxide, and the general chemical formula of the lithium-containing metal oxide is LiNi 1-x-y Co x Mn y O2, where 0≤x≤0.5, 0≤y≤0.

5.

9. The all-solid-state battery according to claim 1, characterized in that: The negative electrode active material contained in the negative electrode sheet is at least one of lithium metal and lithium alloy.

Citation Information

Patent Citations

  • Polymer battery

    JP1999185817A